(untitled) (Biological Sciences - PJSIR, 2002)
A comparative ecological study of phytoplankton of Lake Bakar, district Sanghar and Lake Phoosna, district Badin was carried out during August, 1993 to July, 1996. A total of 78 species belonging to 33 genera of 5 classes (Bacillariophyceae, Chrysophyceae, Dinophyceae , Xanthophyceae and Euglenophyceae) were recorded. 12 species were common in both Lakes. 58 species were present in Lake Bakar and 8 in Lake Phoosna. The study showed that the aquatic environment of Lake Bakar is qualitatively much better as compared to Lake Phoosna.